Couve-crespa hidropônica: efeitos de espaçamentos e número de plantas por célula - Noboa, Caio Salvador (2021)
The consumption of kale is increasing in Brazil, and curly kale, which has a high nutritional value, is not widespread. Kale is sold in bunches of adult leaves, however, there is the possibility of growing in bunches of young plants in a hydroponic system, which has several advantages, however, densities have not been tested. Thus, the aim was to generate information about the hydroponic cultivation in NFT of curly kale in bunches of young plants, with a study of spacing (0.07; 0.11; 0.15; and 0.20 m) and number of plants per cell (one, two, three, and four), in different seasons (winter and summer), aiming to improve the productivity, quality, and homogeneity of kale. In winter, plant height was higher with smaller spacing; nutrient, ash, fiber, and lipid contents were within normal limits; moisture, protein and total carbohydrate contents were lower than those reported for curly kale, but similar to those reported for collards. In summer, there was no statistical difference in plant height. In both periods, with the smaller spacing the higher was the productivity; with less plants per cell the larger were the leaf dimensions and the more homogeneous were the different plants of the same cell. Thus, the desired product in the cultivation of hydroponic kale in bunches of young plants is decisive for choosing spacing and numbers of plants per cell, since different choices bring different productivities, number and sizes of leaves. The hydroponic system is technically viable for curly kale production throughout the year, providing plants of good nutritional quality.